Pengajaran Kosakata Bahasa Inggris Menggunakan Lagu di Panti Asuhan Glorieux, Kefamenanu, Kabupaten Timor Tengah Utara-NTT - Neno, Hesni; Seran, Yanuarius (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
In 2018, a YouTuber revealed that many important information on Google was written in English than in Indonesian. For example, there were 475,000 articles in Indonesian about red spots on the skin, while in English, there were 10.6 million articles which means 23 times more. Another example, dengue fever was found in 1.7 million articles written in Indonesian, while in English, there were 3.4 million articles. Topic around History was found in 92.6 million articles in Indonesian, while in English is 49 times more, it was around 4.6 billion articles. The Youtuber conveyed many important topics that are rarely written in Indonesian, so we have to look for them in English. English is the mother of all information in this digital era. Realizing the importance of English, community service activity was carried out at the Gloriuex Kefamenanu Orphanage, TTU. The authors used English songs as the medium to raise children’s enthusiastic in learning English to have faster and more natural process. The method used is pre-teaching vocabulary (Carney, 1984), and a 3-stage method, namely the preparation stage, core stage, and follow-up stage (Millington, 2011). The result of this service is the motivation to learn English is raising up so that there is an increasing in vocabulary as well.